Motive [compact disc, unabridged] : an Alex Delaware novel - Kellerman, Jonathan (Kellerman, Jonathan. Alex Delaware novels., 2015)
Even having hundreds of closed cases to his credit can't keep LAPD police lieutenant Milo Sturgis from agonizing over the crimes that don't get solved, and the victims who go without justice. Victims like Katherine Hennepin, a young woman strangled and stabbed in her home. A single suspect with a solid alibi leads to a dead end; one even Alex Delaware's expert insight can't explain. The only thing to do is move on to the next murder case; because there's always a next one.